PEMBELAJARAN MUSIK MUATAN LOKAL MELALUI METODE TUTOR SEBAYA DI KELAS VII 1 SMP NEGERI 25 PADANG - Irman, Resky Nur; Syeilendra, Syeilendra (SENDRATASIK UNP, 2019)
Abstract The purpose of this study is to describe the implementation of talempong pacik music learning through the peer tutoring method at class VII-1 in SMP Negeri 25 Padang. This type of study was descriptive with using a qualitative method approach. The object of study was the students at class VII-1  and techniques of data collection were done by taking observation, literature study, interviews and documentation studies. Meanwhile, techniques of data analysis were done by classifying, analyzing descriptively and arranging them systematically. The result shows that local music learningat class VII-1 is not in accordance with the learning objectives, due to several obstacles, namely the learning media and the school only has five talempong so that in the practicum process the talempong pacik music is not well served, which causes several groups are not served well  and it causes they are not able to play talempong musical instruments. The other side of the teacher's competence in the use of learning methods and how to motivate the students in practicing music so that there are some students who do not understand the mastery of Talempong playing technique. In addition, based on the results of UH in general, the students who do not complete this lesson are 21 and only 7 students can complete this test.  Based on the explanation above, it can be concluded that the learning of cultural artat class VII-1  in SMP Negeri 25 Padang has not been carried out properly in accordance with the teacher's RPP. Keywords: learning music, local content, peer tutor